Pelabelan Total Super (a,d)-sisi Antimagic pada Gabungan Saling Lepas Graf Bintang dengan Teknik Pewarnaan Titik - Wardani M, Devi Eka; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
For a graph G=(V,E), a bijection f from V(G) cup E(G) into 1, 2,3,ldots, |V(G)|+|E(G)| is called (a,d)-edge-antimagic totalÂ labeling of G if the edge-weights w(xy) = g(x) + g(y) + g(xy), xy in E(G), form an arithmetic progression starting from a and having common difference d. An (a,d)-edge-antimagic total labeling is called super (a,d)-edge-antimagic total labeling if g(V(G))= 1, 2,ldots,|V(G)|. A vertex coloring is an assignment of labels or colors to each vertex of a graph such that there is no two adjacent vertices have the same colors. We can use vertex coloring technique to label the vertices of a graph such that it has EAV-weight. Furthermore, If we have an EAV-weight of S_n, we can construct a super (a,d)-edge antimagic total labeling of Star Graph, either simple or disjoint union of this graph.